The uptake of presymptomatic genetic testing in hereditary breast-ovarian cancer and Lynch syndrome: a systematic review of the literature and implications for clinical practice - Menko, Fred H; ter Stege, Jacqueline A; van der Kolk, Lizet E; Jeanson, Kiki N; Schats, Winnie; Moha, Daoud Ait; Bleiker, Eveline M A (Familial cancer, 2019)
Following the identification in a proband of a germline BRCA1 / BRCA2 mutation in hereditary breast-ovarian cancer (HBOC) or a DNA mismatch repair gene mutation in Lynch syndrome (LS) he or she will be asked to inform at-risk family members about the option for presymptomatic DNA testing. However, in clinical practice multiple factors may complicate the process of information sharing. We critically evaluated studies on the uptake of presymptomatic genetic testing in both syndromes. A search of relevant MeSH terms and key words in PubMed, Embase and PsycINFO yielded 795 articles published between 2001 and 2017. Thirty of these publications included outcome measures relevant for the current study. Based on information provided by the proband (15 studies) the uptake of presymptomatic genetic testing ranged from 15 to 57% in HBOC, while one study in LS kindreds reported an uptake of 70%. Based on information provided by genetics centres (the remaining 15 studies) the uptake ranged from 21 to 44% in HBOC and from 41 to 94% in LS. However, when genetics centres contacted relatives directly a substantial number of additional family members could be tested. Proband-mediated provision of information to at-risk relatives is a standard procedure in hereditary breast-ovarian cancer and Lynch syndrome. However, the resulting uptake of presymptomatic testing is disappointing—an issue that is now urgent due to the increased use of genetic testing in clinical oncology. We propose that additional strategies should be introduced including the geneticist directly contacting relatives. The outcomes of these strategies should be carefully monitored and evaluated.